Protective effect of cinnamon extract against cobalt-induced multiple organ damage in rats - Isik, Bahar; Suleyman, Bahadir; Mammadov, Renad; Bulut, Seval; Yavuzer, Bulent; Altuner, Durdu; Coban, Taha Abdulkadir; Suleyman, Halis (Frontiers in Pharmacology, 2024)
The role of oxidative stress and inflammation in cobalt (Co) toxicity has been the focus of previous studies. Cinnamon and its main components have been reported to have protective effects in various tissues with antioxidant and anti-inflammatory effects.Aims: In this study, the protective effect of cinnamon extract (CE) against possible Coinduced heart, kidney, and liver damage in rats was investigated biochemically.Methods: Eighteen albino Wistar type male rats were categorized into three groups (n=6 per group): control (CG), CoCL2 administered (CoCL2), and CE+CoCL2 administered (CE+Co).CECoCL2 group administered CE (100 mg/kg), CoCL2 and CG administered distilled water orally by gavage. One hour after the administration, Co (150 mg/kg) was administered orally to CE+CoCL2 and CoCL2 groups. This procedure was repeated once daily for 7 days. Then, biochemical markers were studied in the excised heart, kidney, and liver tissues. Results: CoCL2 increased oxidants and proinflammatory cytokines and decreased antioxidants in the heart, kidney, and liver tissues. Heart, kidney, and liver tissue were affected by Co damage. CE treatment suppressed the CoCL2-induced increase in oxidant and proinflammatory cytokines and decrease in antioxidants in heart, kidney and liver tissues.CE treatment has been shown to attenuate cardiac damage by reducing serum troponin I (TpI) and creatine kinase-MB (CK-MB), renal damage by reducing creatinine and blood urea nitrogen (BUN), and liver damage by reducing alanine aminotransferase (ALT) and aspartate aminotransferase (AST).Conclusions: Co induced the production of oxidant and proinflammatory parameters and antioxidant depletion in heart, kidney, and liver tissues of rats. Our experimental results show that CE protects heart, kidney, and liver tissues against oxidative and inflammatory changes induced by CoCLl2.